First Report of Legionella Pneumophila Serogroup 1 Isolate from Public-Supply Water in Bangladesh - Haque, Anwarul; Yoshizumi, Ayumi; Yoshizumi, Ayumi; Saga, Tomoo; Ohno, Akira; Ishii, Yoshikazu; Tateda, Kazuhiro (The Asia Journal of Applied Microbiology, 2016)
Legionella pneumophila infection is generally recognized to be transmitted from aquatic sources to human. In Bangladesh, although suspected cases of legionellosis were reported, epidemiology of Legionella infection as well as water resource contamination by Legionella spp. was almost unknown. In the current study, we screened water samples from Dhaka, Bangladesh, for Legionella spp. One L. pneumophila isolate was recovered from tap water of a residential hotel. This isolate was identified as serogroup 1 by serum agglutination reaction, and sequence type 1 (ST1) by sequence based typing. Analysis of lipopolysaccharide synthesis cluster genes by PCR revealed lag-1 gene was not detected in this isolate, and its predicted monoclonal antibody subgroup was OLDA/Oxford. This is the first report of isolation and characterization of L. pneumophila from aquatic environment in Bangladesh.